The Position Of The Ppat Deed In The Preparation Of Deeds Related To Money Laundering - Noor, Aslan; Safriani, Vini Nurul; Barus, Theresia Juliana Ngarakken; Tarigan, Notora (UNIVERSITAS PAKUAN, 2025)
This study aims to analyse the position of Land Deed Officers (PPAT) in legal actions related to money laundering. The research method used is a normative legal approach. The results of the analysis show that formally, PPAT deeds remain valid as long as they meet the requirements specified by law. However, if the deed is used to facilitate money laundering practices, it can be used as evidence in court, and the property transferred through the deed may be confiscated by the state. Thus, the status of PPAT deeds in the context of money laundering is recognised, but their application may be overridden by a court ruling. PPATs bear a significant responsibility in preventing such practices by applying the principles of due diligence and the